THE ROLE OF INVESTOR SENTIMENT ON PRICING EFFECT OF PROFITABILITY RISK FACTOR IN KENYA - Mugenda, Nebat Galo; Olweny, Tobias; Wepukhulu, Joshua M. (International Journal of Accounting & Finance Review, 2022)
Emerging stock markets are characterized by strong investor sentiment and rapid fluctuations in returns. However, the role of investor sentiment on asset pricing has not been explored in these markets. This study sought to establish if the effect of the profitability risk factor on stock returns would vary with the level of investor sentiment at the Kenyan equity market. A quantitative causal time-series design was adopted to analyze the cause-effect relationship among the study variables. The study utilized monthly equity return data on 60 firms listed at the Nairobi Securities Exchange (NSE) from 2011 to 2019. Test portfolios were constructed following the Fama-French five-factor model framework. Auto-Regressive Distributed Lag (ARDL) and Vector Error Correction (VEC) estimation techniques show that profitability risk factor is a significant predictor of stock returns at a 5% level. Overall, though not consistent with valuation theory, the coefficient on profitability risk factor is negative, implying a high exposure to profitability risk results in low returns. Further, adding sentiment variables to the main effects model would enhance the significance of the profitability risk factor at the NSE. The evidence presented contributes to establishing investment strategies, estimating the required rate of return and assessing portfolio performance of collective investments. JEL Classification Codes: C32, G11, G12, G14, G41.